Intellectual Capital and its relation with the business result of CMAC - Trujillo: 2017 (SCIÉNDO INGENIUM, 2022)
The present, whose purpose is to address the issue of intellectual capital, in order to determine its true value in a financial institution of our milieu, has raised the following question: What relationship exists between the intellectual capital and the business result of the Municipal Savings and Credit Fund of Trujillo SA, and the hypothesis: There is a direct relationship between pre-test and post-test of the Intellectual Capital and the business result of Caja, The study population was the set of 39 directors of the fund. Thus, the Pre experimental design of a single was used, where the same group acts as experiment group and control group. The method used was deductive - hypothetical and analytical - synthetic; the techniques used were the survey and documentary. The most important findings were: that there is a direct relationship between pre-test and post-test of Intellectual Capital plus the business result of Caja managing to increase through the last three relevant factors such as human, structural and relational. Recommended: The Caja should regularize policies for the consolidation of intellectual capital, internally and externally, and disseminate them in order to be accepted and identified by stakeholders, through the planning and execution of a constant updating project to support the demanding teamwork of the market.
Keywords: Human talent retention strategies; job satisfaction; total reward strategy